Efficient synthesis of benzofuranones: N-heterocyclic carbene (NHC)/base-catalyzed hydroacylation-stetter-rearrangement cascade - Padmanaban, Mohan; Biju, Akkattu T.; Glorius, Frank (Organic Letters, 2011)
A N-heterocyclic carbene/base-catalyzed cascade reaction leading to the formation of functionalized benzofuranones is reported. The reaction proceeds via an intramolecular hydroacylation of unactivated alkynes followed by an intermolecular Stetter reaction and a base-catalyzed chromanone to benzofuranone rearrangement.

N-Heterocyclic carbene catalyzed umpolung of michael acceptors for intermolecular reactions - Biju, Akkattu T.; Padmanaban, Mohan; Wurz, Nathalie E.; Glorius, Frank (Angewandte Chemie-International Edition, 2011)
eahciM! The N-heterocyclic carbene catalyzed umpolung of Michael acceptors proceeds through the formation of a deoxy-Breslow intermediate (see scheme; EWG=electron-withdrawing group). This nucleophilic species can react with other Michael acceptors in an intermolecular fashion, thereby resulting in the formation of homo- or heterodimeric olefins. This “Michael umpolung” should become a valuable method for the formation of densely functionalized olefins.
Keywords: carbenes; Michael acceptors; nitrogen heterocycles; organocatalysis; umpolung

N-heterocyclic carbene-catalyzed cross-coupling of aromatic aldehydes with activated alkyl halides - Padmanaban, Mohan; Biju, Akkattu T.; Glorius, Frank (Organic Letters, 2011)
N-Heterocyclic carbene-catalyzed umpolung of aldehydes followed by their interception with diarylbromomethanes has been reported. This conceptually novel transition-metal-free cross-coupling of aldehydes with alkyl halides works well at low catalyst loadings and under mild reaction conditions leading to the formation of diaryl acetophenone derivatives in good yields. In addition, α-halo ketones and esters can also be used as aldehyde reaction partners.